Basic organizational behavior - Schermerhorn, John R. (John Wiley & Sons, 1998)
A brief introduction to organizational behavior (OB) that tackles the issues facing today's managers, such as diversity, total quality management, ethics and the global marketplace. It uses a unique managerial perspective to explore how a manager uses OB insights in the workplace.